Faktor-Faktor Yang Mempengaruhi Capital Adequacy Ratio (CAR) Bank Umum Syariah di Indonesia - Yeano Dwi Andhika; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
Capital adequacy regulation imposed on banks, including Islamic banks, is part of the regulators’ efforts to ensure that banks have adequate capital in order to get them prepared facing the risks that might arise in their operations. This research aims to find the effects of Islamic banks’ specific variables on Capital Adequacy Ratio (CAR), the capital adequacy indicator in banks.Using panel data regression, this research investigates the possible effects of four bank spesific variables which are Bank Size (LNSIZE), Non-Performing Financing (NPF), Return on Equity (ROE), and Financing to Deposit Ratio (FDR) on Capital Adequacy Ratio (CAR). There are 11 Indonesia’s Islamic commercial banks during 2011 to 2015 used as sample. As Fixed Effect Model (FEM) chosen to be the estimation model, this research indicates that LNSIZE, NPF, ROE and FDR have significant effects on CAR with different level of significance.